The Communist Revolt in Tallinn on the 1st of December 1924 and its Diplomatic Cover-Up - Butkus, Zenonas (Lietuvos istorijos studijos, 2019)
This article, based on the archives stored in Estonia, Latvia, Lithuania, and Russia and some recently published documents, investigates the coup attempted by the Soviets on December 1, 1924 in Tallinn and evaluates its consequences within the broad context of international relations. During the research, it was established that an attempt to stage a coup in Estonia had been undertaken both by the Estonian communists and the USSR leadership, which had the highest political body – the Politburo – and the Comintern, a self-crafted tool set up for spreading the communist movement around the world, at its disposal. Thus, the revolution was masterminded by the Soviet authorities, whereas the Estonian communists were mainly responsible for its implementation. The task of the coup leadership was to seize power and hold on to it for some time, long enough to request that the USSR “renders support.” Preparations were underway for such support. This is evidenced by military preparations in the northern regions of the USSR and the territory near the Estonian border as well as by the deployment of Soviet ships in the vicinity of Tallinn and the activities of the Soviet embassy located in the capital. The attempted coup turned into a putsch due to the maximum conspiracy of their organizers. The conspiracy was brought about by the then-public awareness that the revolutionary events in Germany in 1923 had been instigated by the Soviets. The attempted coup in Estonia failed due to the extraordinary defensive operations put up by the Estonian authorities and power structures as well as due to the failure to involve the workers and the other strata of society in the coup. Latvia, Estonia’s only ally, was the first country to stand by Estonia’s side after the country withstood the attempted coup. The lessons were learnt not only by these two countries but by Lithuania as well. They began taking adequate measures to stifle communist activities. Neither France nor England or any other Western state made plans to deploy their fleets to the Baltic Sea to support the Estonians or at least show, in a demonstrative way, their support in such a trying time. They also failed to hold any diplomatic démarches against the Soviets opposing the export of revolution practiced by the Soviets. Due to diplomatic pressure imposed by the USSR, Estonia could not publicly and officially name the actual organizers of the putsch. As a result, only the local communists were indiscriminately accused. Such forced tactics, if only indirectly, had at least partially been influencing the area of historical research as well. However, the sudden and unequivocal liquidation of the putsch in Tallinn could have prompted the USSR to no longer expand its revolutionary export to the West, and the “abstinence” of such kind had lasted until the Second World War. The war itself and the previous collusion with Adolf Hitler made it possible for Stalin to cherish even greater ambitions to renew the spread of communism in other countries.